The course of chronic itch in hemodialysis patients: results of a 4-year follow-up study of GEHIS (German Epidemiological Hemodialysis Itch Study) - Plewig, Natalie; Ofenloch, Robert; Mettang, Thomas; Weisshaar, Elke (Journal of the European Academy of Dermatology and Venereology, 2019)
Chronic itch (CI) is a frequent symptom in hemodialysis (HD) patients. Previous studies demonstrated great impairments of general well-being and health-related quality of life (HRQOL) as well as a higher mortality in those suffering from CI. Objective The German Epidemiological Hemodialysis Itch Study (GEHIS) is a representative cohort of HD patients in Germany. All patients were followed up 4 years later. The current analyses present data on the course of CI in HD patients, its associated factors including comorbidities, laboratory values and HRQOL. Methods We assessed sociodemographic data, routine laboratory values, comorbidities, HRQOL (SF-12), depression and anxiety (HADS), sleep (duration and quality) and in those suffering from CI characteristics, intensity of CI and itch-related quality of life (ItchyQoL). Those with CI were offered a dermatological examination and CI was classified according to the IFSI classification. Patients were asked if they had consulted a physician about CI. Results Of the patients who had suffered from CI in 2013 (n = 234), 90.5% (212) patients could be followed up. About 36.3% (n = 85) had died, 9.8% (n = 23) had received a kidney transplant in the meantime. A total of 52 HD patients still suffered from CI, in 52 CI had stopped. Those patients still suffering from CI (n = 52) reported a higher mean itch intensity, lower ItchyQoL, higher levels of anxiety and a lower mean sleeping time in 2013. On the other hand, those who did not suffer from CI anymore showed a significant increase of HRQOL compared to 2013. There was no significant difference in dialysis characteristics and laboratory values except for albumin. Only a minority of patients in HD had consulted a dermatologist because of CI (29.9%). Conclusion Our data demonstrate that CI is a persisting symptom in 50% of the HD patients and when it disappears HRQOL recovers. We confirm that CI is a disregarded symptom in HD patients.